Instruments to Measure Health Literacy among Children: A Scoping Review - Abdillah, Ina Laela; Lusmilasari, Lely; Hartini, Sri (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: Research related to health literacy among children is limited due to the lack of appropriate measurement tools for this population. The measurement tools used to measure health literacy among children are usually adapted from the adult versions. Researches related to instruments measuring health literacy that can be used for children in school environments are inadequate. This study aimed to synthesize research on the instruments that measure health literacy among children in the community setting. Method: We carried out a scoping review to synthesize research on the instruments measuring health literacy among children in the community setting. The article searching process was targeted to collect articles with corresponding populations, concepts, and contexts. The search was conducted through PubMed, ProQuest, ScienceDirect, and Sage Journals databases published between 2010- 2020. The selection process was done using Preferred Reporting Items for Systematic Reviews and Meta-Analyses methods (PRISMA). The following critical appraisal used The Joanna Briggs Institute checklist. Results: Out of 328 studies, six articles were selected for this review. Consensus showed that health literacy needs to be applied in various situations. Improving the health literacy of children in the early stages is crucial for children's development and personal health. Several instruments can be applied to measure health literacy in school-age children, such as Health Literacy Measures for Adolescents, Health Literacy for School-aged Children in the English, Turkish and Lithuanian versions, and Chinese version of the eight-item Health Literacy Assessment Tool. Generally, the instruments are adequate, while only two instruments in this study are inadequate because they do not describe the validity and reliability.